2017
DOI: 10.1177/1359105317733535
|View full text |Cite
|
Sign up to set email alerts
|

The mediating effect of neighbor relationship between community social support and elderly’s subjective well-being in China

Abstract: This study aimed to investigate the relationship between community social support, neighbor relationship, and the subjective well-being of the elderly in China. Structural equation modeling was used to test the hypothesized model based on a sample of 2732 senior adults from 2010 Chinese General Social Survey. Results showed that community social support could indirectly affect the subjective well-being of the elderly through the complete mediating effect of neighbor relationship, although there was no signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 53 publications
4
26
0
Order By: Relevance
“…This study found no significant difference for neighbors' purchase history presence or absence on post-'90s perceived enjoyment. Although extant research claimed that closely networked people could influence a person's happiness (Huppert et al, 2005;Jiang et al, 2017;Rath and Harter, 2019), the result is in line with Weiss (2013) that people dislike invasion of privacy when their personal information is used to promote products. Therefore, it can be explained that Chinese post-'90s might have found it unpleasant that their personal information such as a home address is used to provide the recommendation from big corporations like Taobao e-commerce.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…This study found no significant difference for neighbors' purchase history presence or absence on post-'90s perceived enjoyment. Although extant research claimed that closely networked people could influence a person's happiness (Huppert et al, 2005;Jiang et al, 2017;Rath and Harter, 2019), the result is in line with Weiss (2013) that people dislike invasion of privacy when their personal information is used to promote products. Therefore, it can be explained that Chinese post-'90s might have found it unpleasant that their personal information such as a home address is used to provide the recommendation from big corporations like Taobao e-commerce.…”
Section: Discussionmentioning
confidence: 72%
“…Rath and Harter (2019), also pointed out that people's entire social network affects well-being, and that next-door neighbors' well-being has an impact on others' well-being. In addition, Jiang et al (2017) revealed that neighbor relationships can indirectly influence the subjective well-being of the elderly in China.…”
Section: Hypothesismentioning
confidence: 99%
“…Conventional research has been verified that received neighboring behavior, as a type of support, is part of social capital and constructively provides practical help to individuals. 6,7 The given neighboring behavior (NBG)'s impact on conflicts is often positive and can serve as a means of resource acquisition. First, helping neighbors with their problems is a process of social exchange.…”
Section: Introductionmentioning
confidence: 99%
“…11 Neighborhood frequently complements residents' network that exists in their residential environment. 6 Neighbors' close spatial position makes them uniquely poised to help each other, both instrumentally and emotionally. 12 It is a bidirectional rather than a unidirectional process to develop and maintain a social relationship.…”
Section: Introductionmentioning
confidence: 99%
“…As a type of support, it is easy for individuals to get direct and practical help via received neighboring behavior. 5,6 However, these studies mostly concentrated on social support for the old and weak in homogenous communities. 5,7 In contrast, the positive roles neighbors exert in heterogeneous communities have been investigated rarely.…”
Section: Introductionmentioning
confidence: 99%